PERSONALISASI PEMBELAJARAN BERBASIS AI UNTUK TRANSFORMASI MENUJU PENDIDIKAN ABAD 21 YANG BERPUSAT KEPADA SISWA - Marina Elfera; Rahmawari Azril; Ta Ali; Titi Sriwahyuni (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
The primary objective of this research is to analyze the transformative role of Artificial Intelligence (AI)-based personalized learning in shifting the traditional education model towards student-centered 21st-century learning. The core problem addressed in this study is the failure of traditional education models to accommodate the diverse learning styles, speeds, and needs of students. This failure hinders the crucial development of 21st-century skills such as critical thinking and students' personalized potential.The methodology employed is a systematic literature review, focusing on the principles and applications of AI in education, specifically on the implementation of adaptive learning systems, predictive diagnostics, and AI-based intelligent content curation.Key findings indicate that AI facilitates deep personalization, which was previously unattainable by human instructors alone. AI systems facilitate profound personalization through three main mechanisms: real-time diagnostics and targeted interventions, automatic curriculum adjustment to ensure competency mastery, and the fostering of student autonomy. The integration of AI effectively optimizes the role of teachers to focus on mentorship, while also fostering students' independence and ownership over their learning process.Thus, AI-based personalized learning is a crucial structural element for achieving modern educational goals, ensuring that every student can maximize their competencies. This study concludes that AI-powered personalized learning is not merely a technological enhancement but an essential structural component required to actualize the goals of modern, student-centered 21st-century education.